Do changes in weight status affect cognitive function in children and adolescents with obesity? A secondary analysis of a clinical trial. Issue 2 (3rd February 2019) - Anderson, Yvonne C; Kirkpatrick, Kaye; Dolan, Gerard M S; Wouldes, Trecia A; Grant, Cameron C; Cave, Tami L; Wild, Cervantée E K; Derraik, José G B; Cutfield, Wayne S; Hofman, Paul L
Abstract : Objectives: It is unclear whether an association exists between obesity in children/adolescents and cognitive function, and whether the latter can be altered by body mass index (BMI) standard deviation score (SDS) reductions. We aimed to determine whether an association exists between BMI SDS and cognitive function in children/adolescents with obesity engaged in an obesity intervention. Second, we sought to determine if BMI SDS reduction at 12 months was associated with improved cognitive function. Design: Secondary analysis of a clinical trial. Participants: Participants (n=69) were recruited from an obesity intervention. Eligible participants (recruited June 2013 to June 2015) were aged 6–16 years, with a BMI ≥98th centile or BMI >91st centile with weight-related comorbidities. Outcome measures: Primary outcome measure was change in BMI SDS from baseline at 12 months. Dependent variables of cognitive functioning and school achievement were assessed at baseline and 12 months, using dependent variables of cognitive functioning (elements of Ravens Standard Progressive Matrices, Wide Range Achievement Test-fourth edition and Wechsler Intelligence Scale for Children-fourth edition). Results: At baseline, BMI SDS was not associated with all aspects of cognitive function tested (n=69). Reductions in BMI SDS over time did not alter cognitive function overall. However, there was a greater reduction in comprehension standard scores in participants who increased their BMI SDS (adjusted estimated difference −6.1, 95% CI −11.6 to −0.6; p=0.03). Conclusions: There were no observed associations between BMI SDS and cognitive function in participants, apart from comprehension in the exploratory analyses, which may have been a random finding. Further studies need to include larger longitudinal cohorts incorporating a wider BMI range at entry to determine whether our findings persist. Trial registration number: ANZCTR12611000862943; Pre-results.